Diagnostic accuracy of computer aided electrocardiogram analysis in dogs - Estrada, A. H.; Spake, A.; Kleman, M. E.; Leeder, D.; Blischok‐Lapekas, D.; Margiocco, M.; Gentile‐Solomon, J.; Piscitelli, N.; Szlosek, D. (Journal of small animal practice, 2021)
Objectives Evaluation of a computerised electrocardiogram algorithm compared to the interpretation of a team of board‐certified veterinary cardiologists. Materials and Methods This was a cross‐sectional retrospective cohort study. A total of 399 electronic canine electrocardiogram recordings screened from 1391 electrocardiograms were enrolled in the study. A panel of seven cardiologists, masked to patient information, evaluated electrocardiograms for the following: P‐wave amplitude and duration; PR‐interval; R‐wave amplitude; QRS duration; heart rate; mean electrical axis; and final overall diagnosis for the detection of arrhythmia and any abnormal electrocardiogram anomaly. Results The sensitivity of the electrocardiogram algorithm for detecting arrhythmias was 99.7% (95% confidence intervals, CI: 98.5 to 99.9) and the specificity was 99.5% (95% CI: 98.0 to 99.9) compared to the consensus result created by panel of cardiologists. The sensitivity of the algorithm for the detection of any electrocardiogram anomaly, including abnormal measurements, was 71.3% (95% CI: 65.5 to 76.7) and the specificity was 35.1% (95% CI: 27.0 to 43.8) compared to the panel of cardiologists. Clinical Significance The electrocardiogram algorithm was shown to have high sensitivity for the detection of arrhythmias, but not all electrocardiogram anomalies. The results support the use of this algorithm as a tool to aid in the triage of the electrocardiogram workflow.